2012
DOI: 10.1136/gutjnl-2011-301625
|View full text |Cite
|
Sign up to set email alerts
|

CagA mediates epigenetic regulation to attenuate let-7 expression inHelicobacter pylori-related carcinogenesis

Abstract: H pylori CagA induces aberrant epigenetic silencing of let-7 expression, leading to Ras upregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
83
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 48 publications
4
83
0
2
Order By: Relevance
“…MiRNAs were found to be dysregulated in several human cancers including GC [16,17,18]. Han reported that miR-29c acts as a tumor suppressor in GC by directly targeting ITGB1 [16].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs were found to be dysregulated in several human cancers including GC [16,17,18]. Han reported that miR-29c acts as a tumor suppressor in GC by directly targeting ITGB1 [16].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-associated miR-7 and miR-146a are deregulated by inflammation factors that are produced through the interaction between CagA and the host cell ( fig. 1) [2][3][4][5][6].Epigenetic regulation of miRNAs is also important for deregulation of miRNAs in gastric cancer. DNA hypomethylation and promoter methylation change the miRNA expression profile; the former causes miR-196b overexpression and the latter results in down-regulation of miR-124a [7][8].…”
mentioning
confidence: 99%
“…Tumor-associated miR-7 and miR-146a are deregulated by inflammation factors that are produced through the interaction between CagA and the host cell ( fig. 1) [2][3][4][5][6].…”
mentioning
confidence: 99%
“…In addition, novel risk markers of gastric cancer were identified by the microarray analysis for hypermethylated CpG islands [129]. A recent study revealed that CagA of H. pylori causes aberrant epigenetic silencing of let-7 followed by upregulation of Ras oncoprotein using in vitro experiments and an in vivo mouse model [130].…”
Section: Epigeneticsmentioning
confidence: 99%